Sistem Pendukung Keputusan Pemilihan Lembaga Bimbingan Belajar Menggunakan Pembotoan Rank Sum dan Pendekatan WASPAS - Mabrur, Nur Shobi; Humaera B, Nurul; Alfian; Mulyadi; Sandra Dewi Saraswati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The demand for supplementary education has increased along with the intense academic competition, making tutoring centers an essential solution. However, the selection of tutoring centers often faces challenges such as the abundance of alternatives, the lack of structured methods, and subjective decision-making. The aim of this study is to design and develop a Decision Support System (DSS) based on the Rank Sum and WASPAS approaches as a foundation for supporting the objective selection process of tutoring centers. The Rank Sum method is employed to determine the weights of criteria based on their priority levels, while the WASPAS method is used to evaluate alternatives by integrating criteria weights and alternative performance. The system is implemented as a web-based application that facilitates the management of criteria, alternatives, and computations to generate the best alternative recommendations. A case study reveals that the Ganesha Operation alternative ranks the highest with a score of 0.8739, followed by Nurul Fikri (0.8595), Primagama (0.8501), Neutron (0.8394), and Inten (0.8223). Black-box testing indicates that all system features function effectively and meet the specified requirements. This demonstrates that the designed system provides functionality aligned with its design and user needs. The contributions of this study include the integration of the Rank Sum and WASPAS methods, the implementation of a practical web-based system, and the provision of a methodology applicable to similar case studies across various fields.